1990
DOI: 10.1029/jb095ib10p15829
|View full text |Cite
|
Sign up to set email alerts
|

An in situ X ray diffraction study of the kinetics of the Ni2SiO4 olivine‐spinel transformation

Abstract: Using the “MAX‐80” cubic‐anvil high‐pressure apparatus with synchrotron radiation, X ray diffraction experiments have been carried out to study the kinetics of the Ni2SiO4 olivine‐spinel transformation at 3.6–4.8 GPa and 740°–980°C. The Ni2SiO4 olivine‐spinel equilibrium boundary has also been redetermined. The starting material for the kinetic experiments was Ni2SiO4 olivine which was hot‐pressed in situ at 980°C and 2.5 GPa for 1.5 hours. During the transformation, X ray diffraction patterns were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 45 publications
4
63
1
Order By: Relevance
“…The rate functions k and parameters n determined from kinetic experiments using "wet" coesite varies from 1.2-1248 and 0.12-0.40, respectively. Values of n smaller than one are theoretically not possible and may indicate to the weakness of the simple model of Cahn [3,4]. But, nevertheless the direct comparison of the results of the "wet" and "dry" experiments performed under the same experimental conditions shows that the transformation kinetics of coesite to quartz is several orders of magnitude faster when coesite contains considerable amounts of intrinsic OH.…”
mentioning
confidence: 93%
“…The rate functions k and parameters n determined from kinetic experiments using "wet" coesite varies from 1.2-1248 and 0.12-0.40, respectively. Values of n smaller than one are theoretically not possible and may indicate to the weakness of the simple model of Cahn [3,4]. But, nevertheless the direct comparison of the results of the "wet" and "dry" experiments performed under the same experimental conditions shows that the transformation kinetics of coesite to quartz is several orders of magnitude faster when coesite contains considerable amounts of intrinsic OH.…”
mentioning
confidence: 93%
“…Investigations o n natural ringwoodite and wadsleyite in meteorites ( 8 , 9 ) as well as experiluental studies at high pressure have been carried out to elucidate the nature of these transitions. Most ex~erilnents have been performed o n analog compositions s~l c h as MgLGeO,, NiLSiO,, Fe2Si0,, MgLSiO,, and Co2Si0, (10)(11)(12)(13)(14)(15)(16). These studies indicate that the a-to-y transformation can occur either by incoherent grain bo~rndary n~~c l e a t i o n and interfacecontrolled growth (17), when differential stresses are low and the pressure is fairly close to equilibrium (1 0 , 1 1 , 13, 16), or by an intracrystalline mechanism that is presumed to involve shear (10-12, 14, 15, 18).…”
mentioning
confidence: 99%
“…Experimental data have shown that grain boundary nucleation and interface-controlled growth is the major mechanism of the phase transformation from olivine to wayaslite/ringwood [1,5] . However there is no nucleation rate of olivine phase transformation as yet, people have to employ the data from analogous minerals [6] .…”
Section: Introductionmentioning
confidence: 99%